2021
DOI: 10.1029/2021ef002340
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Studying Diverse Types of Compound Weather and Climate Events

Abstract: Compound weather and climate events are combinations of climate drivers and/or hazards that contribute to societal or environmental risk. Studying compound events often requires a multidisciplinary approach combining domain knowledge of the underlying processes with, for example, statistical methods and climate model outputs. Recently, to aid the development of research on compound events, four compound event types were introduced, namely (a) preconditioned, (b) multivariate, (c) temporally compounding, and (d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 138 publications
(214 reference statements)
2
96
0
1
Order By: Relevance
“…Fundamentally, each organisation manages its objectives through certain measures, such as instruments or tools. Bemelmans-Videc et al (1998) examine various (policy) instruments in different contexts and categorise them in a broad scheme. Policy instruments, also referred to as government tools, can be understood as the application of techniques to how public authorities exercise their power to achieve their goals and to initiate social change.…”
Section: Nato Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Fundamentally, each organisation manages its objectives through certain measures, such as instruments or tools. Bemelmans-Videc et al (1998) examine various (policy) instruments in different contexts and categorise them in a broad scheme. Policy instruments, also referred to as government tools, can be understood as the application of techniques to how public authorities exercise their power to achieve their goals and to initiate social change.…”
Section: Nato Approachmentioning
confidence: 99%
“…The analysis showed that each of the three municipalities created a different nuanced understanding of what a "compound event" means. In particular, the municipalities differ in their perception of what constitutes such a combined incident and what consequences it has for the local management and thus their risk management practices, which is also true for other European countries (Bevacqua et al, 2021). The three municipalities face different experiences, strategies, tools, and challenges in generally handling the risk of flooding and particularly compound flooding.…”
Section: Comparing the Three Municipalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One effort in this direction is the ongoing European Space Agency Climate Change Initiative for Lakes project, which coordinates a range of remote sensing techniques to develop time series data for multiple lake essential climate variables-including lake surface temperature, ice cover, water level/extent, and water-leaving reflectance. These data could allow further studies to explore diverse compound extreme events in lakes (Bevacqua et al 2021), and it provides good prospects for the impact of compound extremes to be better quantified and appreciated at a global scale. Overall, we hope that our contribution will stimulate wider efforts to understand the far-reaching global implications of compound extreme events, and their impacts on aquatic ecosystems.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…These impacts can affect natural or societal systems, and act over spatial or temporal dimensions. Recent advances in theories of compounding (Raymond et al 2020, Thonicke et al 2020, Rusca et al 2021, Simpson et al 2021, in the statistics and dynamics of specific hazards (Bevacqua et al 2021), and in the analysis of co-occurrence of different hazard types (particularly drought and heatwaves; Rogers et al 2021, Singh et al 2021), have enabled an ever wider array of risk scenarios to be considered with sophistication. However, there remains a lack of systematic and cross-scale overviews of potential hazard interaction.…”
Section: Introductionmentioning
confidence: 99%